(3GdQhV GdRGgQ aj efGbH GdTjN YHO GdbGOQ (B( (3GdLjdGfj(B)s - (3HQgGf GdOjf EHQGgje Hf Ydj Hf CMeO GdbGOQi,J (B880 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdHQ GdLhGO GdeGfM dYHGOg eG TGA ef YWGFg s
(3BNQgG (B:s
(3SHMGf QHc QH GdYRI YeG jUahf hSdGe Ydi GdeQSdjf hGdMeO ddg QH GdYGdejf hdG Mhd hdGbhI EdG HGddg GdYdi GdYXje s
(3Vef eLehY , JQJjHgG (B: (3ef U (B1 - (3U(B66s
(3GdVhA GddGeY (B:(3L(B1s
(3U(B80s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B52s
Keywords: (3GdJGQjNs